Ethnobotany Medicinal Plants of Dawan Ethnic in North Central Timor Regency - Noviana Mery Obenu; Emilia Juliyanti Bria (University of Brawijaya, 2021)
The use of medicinal plants is still maintained for generations by the Dawan Tribe in North Central Timor Regency. The loss of knowledge about the use of plants as an alternative treatment of various diseases used by local communities can be caused by the impact of modernization. Therefore, it is necessary to carry out the process of documenting this knowledge. The purpose of this research is to take an inventory of medicinal plants, to know the plant organs used for medicine and how to use the medicine. The method used in this study is a qualitative description method, with several field data collection techniques and identification of medicinal plant species. Data collection techniques include observation, interviews, and exploration. The results of this study indicate that there are 44 species of medicinal plants used, from 25 plant families. The medicinal plant family with a high number of species is the Zingiberaceae family (13.6%). Based on the habitus, 44 species of medicinal plants used consisted of 23 species from trees, 2 species from lianas, 9 species from herbs, 7 species from shrubs, and 3 species from shrubs. In addition, based on plant organs the most widely used as medicine out of 44 plant species, namely the part of the leaf organ (23.91%). Meanwhile, based on the method of use of the 44 species of plants used for medicinal ingredients, the method of drinking has the highest percentage (33.33%) and is usually practiced by the Dawan Tribe.